ON THE PRESENCE OF SUBSTANCES ACTING AS ESTROGENS IN ALFAALFA GROWN IN GREECE - ΔΕΜΕΡΤΖΗΣ, Π. Χ. (Journal of the Hellenic Veterinary Medical Society, 1972)
Experiments were done to determine the estrogen content of samples of Lucerne (Medicago sativa) grown in different areas of Greece. Oestrogens, if present, were below the limits of detection of the biological method used. It is suggested that this subject warrants farther investigation.